2001
DOI: 10.1203/00006450-200102000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Myopathic Form of Very-Long Chain Acyl-CoA Dehydrogenase Deficiency: Evidence for Temperature-Sensitive Mild Mutations in Both Mutant Alleles in a Japanese Girl

Abstract: In a 14-year-old Japanese girl, manifested recurrent myalgia with elevated serum creatine kinase after moderate exercise became evident, and she was diagnosed as having a myopathic form of very-long chain acyl-CoA dehydrogenase deficiency. Her first clinical symptom of the disease was evident when she was 6 y of age. She had never had hypoglycemic attacks, and hepatomegaly and cardiomyopathy were absent. The diagnosis was suspected on the basis of the urinary organic acid profile after a 36-h fast, long-chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Later-onset disease is usually characterized by myopathic symptoms, and onset is in adolescence or adulthood. 5,25 848T…”
Section: Discussionmentioning
confidence: 99%
“…Later-onset disease is usually characterized by myopathic symptoms, and onset is in adolescence or adulthood. 5,25 848T…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 mutations such as missense, small deletion, and abnormal splicing due to insertions of IVS have been identified in ACADVL, and mutations are distributed all over the gene (Gregersen et al 2008). Near the mutation site of the present case, two pathogenic substitutions; p.A416T (c.1246G>A) and p.T409M (c.1226C>T), have been reported (Fukao et al 2001;Isackson et al 2013). Two single nucleotide variations resulting in an amino-acid change before position 414 have also been identified (rs201606472; c.1237A>G, p.I413V and rs143172658; c.1239A>G, p.I413M).…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, the genotype D405H/R450H most likely associates two mild mutations. Indeed, previous studies using transient expression in SV-40 fibroblasts demonstrated that R450H is a mild temperature-sensitive mutation [20]. Furthermore, modeling of D405H showed that the conserved Asp405 is located on the surface of the molecule and that substitution to a hydrophilic His would probably have mild consequences on protein structure and stability.…”
Section: Resultsmentioning
confidence: 99%